The Efficacy of Psilocybin in the Treatment of Depression and Anxiety: A Meta-Analysis - Hodge, Andrew T.; Sukpraprut-Braaten, Suporn; Strayhan, Robert C. (Current Psychiatry Research and Reviews, 2023)
Background: The use of psychedelic compounds to treat psychiatric disorders has become a very significant topic of research over the past several years. Psilocybin has risen to prominence as one of the most studied among these psychedelic compounds. Multiple trials have already shown that it can be a safe and efficacious treatment for various medical conditions. This study intends to perform a meta-analysis of data reported in clinical trials studying psilocybin’s effect on depression and anxiety. Methods: Articles were searched, screened, and ultimately selected using predetermined inclusion criteria. Data was collected from commonly used psychometric tests that measured mood and anxiety symptoms. Effect sizes were calculated by comparing scores in these tests at baseline and control to experimental groups. Sub-group analysis was performed to assess psilocybin’s effect on depression and anxiety during short, medium, and long-term time frames. Results: Statistical significance was achieved in reducing depression and anxiety symptoms compared to controls in multiple subgroups. Heterogeneity of the effect sizes was calculated using an I2 value which showed low to moderate values. Multiple tools were used to assess publication bias, and none could be found. Conclusion: Although research on psilocybin continues to show promise, the evidence is still at a preliminary phase, and more trials need to be conducted with larger patient populations over longer periods for psilocybin to potentially be approved in a community setting.
Keywords: psychedelics